GROUP GUIDANCE SERVICES WITH SELF REGULATION TECHNIQUES FOR STUDENTS - Pranoto, Hadi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Group guidance is an activity of existing services in guidance and counseling is helpful to discuss the topic of problems that are common to both topics task or topic freely discussed the topic of the present that can be taken through the media, such as newspapers, magazines, television, internet and others are discussed groups. With the technique of self-regulation in the group to facilitate members of the group in preparing: (1) planning, (2) self monitoring, (3) self-reflection/ self-evaluation.